Optimization of Two-Wheeled Patrols by the Turjawali Unit of the Samapta Unit in Preventing Motor Vehicle Theft in the Jurisdiction of Semarang Police - Rachma, Warda Aulia (Advances in Police Science Research Journal, 2024)
This final project  research focuses on the implementation of patrols and optimization of two-wheeled patrols of the Turjawali Unit by the Semarang Police Samapta Unit in preventing motor vehicle theft.  This research uses a qualitative approach  with the type of field research by conducting interviews, interviews, and document studies that are  reviewed with the concept of improvement efforts, the concept of patrol, the concept of Samapta, and the concept of theft. The theories used in this study are management theory (POAC), day organization source theory, and SWOT theory. The performance of  two-wheeled patrols was analyzed using POAC (Planning, Organizing, Actuating, and Controlling) management theory and two-wheeled patrol organizational resources were analyzed using 6 M organizational resource theory (Man, Money, Material, Methods, Machine and Market). The results of the research obtained show that a number of obstacles are still found in patrol activities ranging from organizational resources that are not optimal both task executors to the targets to be aimed at in the implementation of two-wheeled patrols. It is also found that the planning, organizing, implementing, and supervision of patrols is less than optimal and less in accordance with Perkabaharkam No.1 of 2017. Factors that affect the implementation of two-wheeled patrols are analyzed using SWOT theory  where there is a balance between the strengths and weaknesses of two-wheeled patrols Satuan samapta Polrestabes Semarang in carrying out patrols. It can be concluded that the implementation of patrols of the Semarang Police Samapta Unit in preventing curanmor has not been maximized because the management process of patrol activities is not optimal as well. It is recommended for the Semarang Police Samapta Unit to improve and maximize the implementation of two-wheeled patrols by utilizing and maximizing human resources, budgets, materials, methods, machines, and patrol targets through new ideas and innovations, especially through existing technological developments.